Selections of set-valued stochastic processes. (1998) - Michta, Mariusz; Rybiński, Longin E.
Abstract : We show that ℱ t -adapted, set-valued stochastic processes satisfying mild continuity conditions admit, ℱ t -adapted, stochastically continuous selections.